Microresonator photonic wire bond integration for Kerr-microcomb generation - Alain Yuji Takabayashi; Nikolay Pavlov; Victoria Rosborough; Galen Hoffman; Lou Kanger; Farzad Mokhtari Koushyar; Taran Huffman; Mike Nelson; Charles Turner; Leif Johansson; Juergen Musolf; Henry Garrett; et al. (Scientific Reports)
Abstract Extremely high-Q microresonators provide an attractive platform for a plethora of photonic applications including optical frequency combs, high-precision metrology, telecommunication, microwave generation, narrow linewidth lasers, and stable frequency references. Moreover, the desire for compactness and a low power threshold for nonlinear phenomena have spurred investigation into integrated and scalable solutions. Historically, crystalline microresonators with Q  $$\sim$$  109 were one of the first material platforms providing unprecedented optical performance in a small form factor. A key challenge, though, with these devices is in finding alternatives to fragile, bulky, and free-space couplers, such as tapered fibers, prisms, and cleaved fibers. Here, we present for the first time, the evanescent coupling of a photonic wire bond (PWB) to a MgF2-based microresonator to generate solitons and a pure, low-noise microwave signal based on Kerr-microcombs. These results open a path towards scalable integration of crystalline microresonators with integrated photonics. Moreover, because PWBs possess advantages over traditional coupling elements in terms of ease of fabrication, size, and flexibility, they constitute a more advanced optical interface for linear and nonlinear photonics.